Iliopsoas Tendon Reformation after Psoas Tendon Release. (15th April 2013) - Garala, K.; Power, R. A.
Abstract : Internal snapping hip syndrome, or psoas tendonitis, is a recognised cause of nonarthritic hip pain. The majority of patients are treated conservatively; however, occasionally patients require surgical intervention. The two surgical options for iliopsoas tendinopathy are step lengthening of the iliopsoas tendon or releasing the tendon at the lesser trochanter. Although unusual, refractory snapping usually occurs soon after tenotomy. We report a case of a 47-year-old active female with internal snapping and pain following an open psoas tenotomy. Postoperatively she was symptom free for 13 years. An MRI arthrogram revealed reformation of a pseudo iliopsoas tendon reinserting into the lesser trochanter. The pain and snapping resolved after repeat iliopsoas tendon release. Reformation of tendons is an uncommon sequela of tenotomies. However the lack of long-term studies makes it difficult to calculate prevalence rates. Tendon reformation should be included in the differential diagnosis of failed tenotomy procedures after a period of symptom relief.